Syntheses, characterisation and vapour pressure of metallo-organic titanium precursor for MOCVD applications - Arockiasamy, S.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mallika, C.; Nagaraja, K. S. (Inorganica Chimica Acta, 2010)
Metallo-organic complexes of titanium such as [Ti(bzac)(2)(O(i)Pr)(2)] (1) and [Ti(bzac)(2)en(O(i)Pr)(2)] (2) were synthesised using 1-phenyl-1,3-butanedione (bzac) and the Schiff's base ligand N, N0-ethylene-bis(1-phenyl-1,3-butanediimine) [(bzac)(2)en]. A novel ligand 1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanone (bzac1a2pol, 3) synthesised by condensing benzoylacetone (bzac) with 1-amino-2-propanol (1a2pol) was used in the synthesis of the complex bis(1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanoato)titanium (IV), [Ti(bzac1a2pol)(2), 4]. These complexes were synthesised by replacing the isopropoxy group (O(i)Pr) of titanium tetra-isopropoxide, Ti(O(i)Pr)(4) by the appropriate ligands. Complexes 1, 2 and 4 were characterised for their volatility/thermal stability using TG/DTA and complex 4 was found to be volatile giving a residue of similar to 5.0% (TG) at 377 degrees C and similar to 3.0% (reduced pressure, 1 mbar) at 285 degrees C. Ligand 3 and its Ti complex 4 were characterised by (1)H NMR, (13)C NMR, elemental analysis, mass spectrometry and single crystal XRD. A value of 164.2 +/- 5.2 kJ mol(-1) for the standard enthalpy of sublimation (Delta H(sub)(0)) was evaluated for 4 from its vapour pressure. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: MOCVD; Single crystal; Syntheses; Ti complexes; Vapour pressures; Volatile complexes